PDGF-AB rich-trombocyte lysate supplementation from breast cancer patients increased the proliferation of breast cancer stem cells (Faculty of Medicine Universitas Indonesia, 2018)
Background: Thrombocytosis in breast cancer (BC) patient was thought to play a role in the invasiveness of breast cancer stem cells (BCSCs). Modification of tumor microenvironment was proposed to increase the efficacy of anticancer therapy. This study was aimed to analyze the effect of platelet lysate (PL) as well as its PDGF-AB content as a tumor microenvironment on (CD24-/CD44+) BCSC proliferation.Methods: This was an experimental study that treated culture of BCSCs with PL from breast cancer (BC) patients or healthy donors. Venous blood from all subjects were subjected to prior hematology test and then processed to obtain platelet rich plasmaÂ (PRP). Platelet counts in PRP were determined. PRP was processed to obtain PL. PDGF-AB contents in PL were measured. PL at concentrations of 0.01% (v/v) was supplemented into DMEM-F12 medium and used for culturing BCSCs (CD24-/CD44+ cells). After 48 hours, total cell count, population doubling time (PDT), and cell viability were calculated and their correlation with platelet count and PDGF-AB levels were analyzed.Results: BC patients (n=5) had higher platelet counts and PDGF-AB levels in PL compared to healthy donors (n=15), (p=0.02). PL from BC patients could stimulate the proliferation of BCSCs higher than healthy donors (p<0.001) and showed lower PDT value (p=0.001). Cell proliferation and PDT showed strong correlation with PDGF-AB level. This observation suggests that PDGF-AB has a role on BCSCs proliferation. PL showed no effect on BCSCs viability.Conclusion: Breast cancer patient platelet lysate stimulated BCSC proliferation.